Something to talk about. modernism, discourse, style (2008)
The article begins with the claim that a series of buildings, texts, and exhibitions built a false image of the modern in architecture which has lead to conceive it as a Style. There are three core themes in the article: first, the reconstruction of this stylistic conception –sponsored by the heirs of Heinrich Wölffing´s ideas on the history of art; second, its theoretical and practical drawbacks, and third, a closing alternative claim proposing a new approach to modernism as a Discourse in itself. That is, modernism not as the result of a discourse but is a debate between different architectural practices and formal conceptions articulated against the backdrop of modernity. Moreover, it claims that modernism in architecture is an ongoing conversation between architecture and society over the possibility of anticipating a better world. The concept of Discourse has been drawn from the social sciences, specially what Jürgen Habermas calls communicative action; and yet, it relies on the findings and intuitions of several generations of architectural research, which have made it possible to conceive the modern as a discourse. The idea of modernism is also drawn from other disciplines: from Emil Durkheim’s sociology where modernism is part of the trilogy modernity-modern-modernism; and from the history of art where modernism is linked to a wide range of categories, including different styles, movements, genres, and means.